A New Method for Numerical Integration of Higher-Order Ordinary Differential Equations Without Losing the Periodic Responses - Katsikadelis, John T. (Frontiers in Built Environment, 2021)
A new numerical method is presented for the solution of initial value problems described by systems of linear ordinary differential equations. Using the state-space representation a differential equation of order is transformed into a system of first-order equations, thus the numerical method developed recently by Katsikadelis for first-order parabolic differential equations can be applied. The stability condition of the numerical scheme is derived and is investigated through several well-corroborated examples, which demonstrate also its convergence and accuracy. The method is simply implemented. It is accurate and has no numerical damping. The stability does not require symmetrical and positive definite coefficient matrices. This advantage is important because the scheme can find the solution of differential equations resulting from methods in which the space discretization does not result in symmetrical matrices, as for example the boundary element method. It captures the periodic behavior of the solution, where many of the standard numerical methods may fail or are highly inaccurate. The present method solves also equations having variable coefficients as well as nonlinear ones. It performs well when motions of long duration are considered and it can be employed for the integration of stiff differential equations as well as equations exhibiting softening where widely used methods may not be effective. The presented examples demonstrate the efficiency and accuracy of the method.